Impact of polyethylene terephthalate microfiber length on cellular responses in the Mediterranean mussel Mytilus galloprovincialis. (June 2021) - Choi, Jin Soo; Kim, Kanghee; Hong, Sang Hee; Park, Kyoung-Il; Park, June-Woo
Abstract: Many studies have investigated the toxic effects of microplastics in marine organisms, but most studied nano-sized round microplastics at high concentrations and were not environmentally relevant. To understand the cellular toxicity of polyethylene terephthalate microfibers (PET-MFs) by length (50 and 100 μm), Mediterranean mussels ( Mytilus galloprovincialis ) were exposed to environmental (0.5 μg/L) and high (100 mg/L) MF concentrations for four days. Short PET-MFs accumulated in the lower intestinal organs of the mussels, but long PET-MFs were only observed in the upper intestinal organs. Both sized PET-MFs affected necrosis, DNA damage, reactive oxygen species, nitric oxide, and acetylcholinesterase (AChE) activity. Significant MF length-dependent effects occurred at environmentally relevant concentrations for DNA damage (100 μm MFs) and AChE activity (50 μm MFs). However, length effects disappeared at the higher exposure concentration. The current study provides potentially sensitive indicators to detect MFs exposure and the ecotoxicological implications of MFs in marine ecosystems. Highlights: Mussels exposed to PET-MFs with different length. PET-MFs affected cellular immune responses in mussels. Short MFs accumulated in lower organs, while long MFs did in upper organs. AChE activity is sensitive to short MFs, while DNA damage to long MFs at environmentally relevant concentration. Length dependent type of toxicity was disappeared at high concentration.